Pengaruh Strategi Know-Want To Know-Learned Terhadap Hasil Belajar Siswa - Fahmi Fakhrudin; Endang Herawan; Nurul Senja Wiraning Fury (UIR Press, 2022)
The purpose of this study was to determine the effect of the know-want to know-learned strategy on student learning outcomes in economics class X at SMA Negeri 2 Majalengka. Based on the results of data collection found a problem, namely the low learning outcomes obtained by class X students at SMA Negeri 2 Majalengka. The purpose of this study was to determine the effect of the know-want to know-learned strategy on student learning outcomes in economics class X at SMA Negeri 2 Majalengka. This research method uses the type of experimental research. The results of the Paired T Test are obtained, namely the tcount value is greater than ttable or the significance value is smaller than zero point zero five indicating that the know-want to know-learned strategy has an effect on learning outcomes and affects learning outcomes in economics subjects in class X in SMA Negeri 2 Majalengka